To interpret the values of Bundo Kanduang in the Internal Control System - Djuharni, Darti (The International Journal of Accounting and Business Society, 2017)
This research is to reveal the value of Bundo Kanduang in Internal Control System. Bundo Kanduang is a nickname given to a woman who can be an example both in the family and in the community. As a role model, many values can be learned and passed on to future generations. Data obtained from this research using etnometodhology, Â then analyzed by using indexicality and reflexivity based on Bundo Kanduangâ€™s values. The findings of this study indicate that the internal control carried out in this business raises the value of "Raso jo pareso" that is using reason and conscience in action